![Logo](/assets/logo-d3f1fdf60522f0983e71f9fcc720cb7da5b55c0b748ed5bded3d2fbf81387bf0.png)
CORD-19:6e2db98aa242e3e84116afdfad5e250943c55ac5 / 43506-43733
Annnotations
CORD-19_Custom_license_subset
{"project":"CORD-19_Custom_license_subset","denotations":[{"id":"T366","span":{"begin":0,"end":227},"obj":"Sentence"}],"text":"Finally, we take the infimums with T max on both sides of the second step conclusion, i.e., T(u, S 1 ∪ S 2 ) ∧ T max = T(u, S 1 ) ∧ T(u, S 2 ) ∧ T max , which means (u, S 1 ∪ S 2 ) = (u, S 1 ) ∧ (u, S 2 ) by the definition of ."}
CORD-19-Sentences
{"project":"CORD-19-Sentences","denotations":[{"id":"TextSentencer_T366","span":{"begin":0,"end":227},"obj":"Sentence"},{"id":"TextSentencer_T366","span":{"begin":0,"end":227},"obj":"Sentence"},{"id":"T67393","span":{"begin":0,"end":227},"obj":"Sentence"}],"namespaces":[{"prefix":"_base","uri":"http://pubannotation.org/ontology/tao.owl#"}],"text":"Finally, we take the infimums with T max on both sides of the second step conclusion, i.e., T(u, S 1 ∪ S 2 ) ∧ T max = T(u, S 1 ) ∧ T(u, S 2 ) ∧ T max , which means (u, S 1 ∪ S 2 ) = (u, S 1 ) ∧ (u, S 2 ) by the definition of ."}